Climate Degradation: A Threat to Mankind and Agriculture - Jain, Dr. Deepali (International Journal on Orange Technologies, 2023)
Climate change is one of the most defining concerns of today’s world and has greatly reshaped or in process of altering earth’s ecosystems. Although climate change has been a constant process on earth, but in recent times, approximately last 100 years or so, the pace of this variation has increased manifolds. Due to the anthropogenic activities the average temperature has risen by 0.9 °C since nineteenth century, mainly due to greenhouse gas (GHG) emissions in the atmosphere. As per estimates this rise is expected to be 1.5 °C by future or may be even more, the way deforestation is occurring, GHG emission is increasing and soil, water bodies and air are being polluted. The unprecedented hike in temperature has resulted in increased events of droughts, floods, irregular patterns of precipitation, heat waves and other extreme happenings throughout the globe.